Common herbal treatments for senile dementia in ancient civilizations: Greco-Roman, Chinese, Indian, and Iranian - Mohammad Mahdi Ahmadian-Attari; Solat Eslami; Leila Dargahi; Ahmad Ali Noorbala (Institue of Medicinal Plants, ACECR, 2020)
Background: Senile dementia is the most common kind of dementia with considerable social and economic costs. Since the nature of disease is multi-pathological, current treatments cannot cover all aspects of the disease. Recently, scientific considerations have focused on the role of natural products, especially those with traditional backgrounds. Objective: to review natural treatments of dementia in ancient Greek, traditional Chinese, Ayurveda, and Iranian traditional medicines with concentration on common herbs concurrently mentioned in two or more than two of them. Methods: Scopus database and primary sources were thoroughly searched for selective keywords. The common herbs concurrently mentioned in two or more than two of the aforementioned traditional medicines were selected to deeply investigate for their active ingredients as well as their mechanisms of actions. Results: The results showed that Acorus calamus, Nardostachys jatamansi, Glycyrrhiza glabra, Phyllanthus emblica, Semencarpus anacardium, Terminalia chebula, and Zingiber officinale had been commonly prescribed for dementia in mentioned traditional systems. According to pharmacological studies, these herbs act their anti-dementia effects via cholinergic, anti-NMDA, antioxidant, anti-inflammatory, anti-apoptotic, and anti-β amyloid activities. Furthermore, 16 active principles of these herbs were identified, including α- and β-asarone, desoxo-narchinol A, narchinol B, glabridin, liquiritigenin, emblicanins A and B, 3, 5, 6, 3chr('39'), 5chr('39'), 6chr('39')-hexahydroxybiphenyl-2, 2chr('39')-dicarboxylic acid, 1chr('39'),2chr('39')-dihydroxy-3chr('39')-pentadec-8-enylbenzene, 1chr('39'),2chr('39')-dihydroxy-3chr('39')-pentadeca-8,11-dienylbenzene, chebulagic acid, and 1,2,3,4,6-penta-O-galloyl-β-d-glucose, Zingipain, 6-gingerol, and 6-shogaol. Conclusion: Chinese, Indian, and Iranian traditional medicine can play a complementary and alternative role in preventing and treating senile dementia. The scientific evidence supports their traditional anti-dementia claims.